Long-term effectiveness of mailed nicotine replacement therapy: study protocol of a randomized controlled trial 5-year follow-up - Vladyslav Kushnir; Peter Selby; Laurie Zawertailo; Rachel F. Tyndale; Scott T. Leatherdale; John A. Cunningham (BMC, 2017)
Abstract Background Our group recently completed a randomized controlled trial, evaluating the efficacy of providing 5 weeks of free nicotine replacement therapy (NRT; in the form of the nicotine patch) by expedited postal mail without behavioral assistance to regular adult smokers interested in receiving it. The findings revealed that mailed provision of nicotine patches resulted in more than a doubling of quit rates at a six-month follow-up compared to a no intervention control group. While this trial provided evidence for the effectiveness of mailed nicotine patches in promoting cessation, the findings speak only to the short term effectiveness of this approach. As relapse to smoking is known to occur beyond the 6 month period, it is important to evaluate whether the net benefit of NRT in naturalistic settings can be maintained long-term. The present study aims to perform a 5-year follow-up survey of participants in the original trial to evaluate the long-term effectiveness of mailed NRT. Methods/Design Trained interviewers will contact participants in the randomized controlled trial 5 years post-enrollment. A total of 924 participants will be eligible to be contacted. Interviewers will first assess participants' smoking status and their level of nicotine dependence. Participants reporting not currently smoking will be asked whether they have smoked tobacco, even a puff, in the last 30 days (primary outcome measure: 30-day point prevalence abstinence), past 6 months (secondary outcome measure: prolonged 6-month abstinence), and since the 8-week follow-up survey (secondary outcome measure: > 4 year continuous abstinence). Interviewers will be blind to experimental condition at the time the primary outcome measure will be assessed. It is hypothesized that participants who received nicotine patches at baseline will display significantly higher quit rates at the 5-year follow-up as compared to participants who did not receive nicotine patches at baseline. Discussion If the study finds that the mailed distribution of free NRT is effective at promoting long-term cessation, it would provide further evidence to move forward with policies designed to make NRT treatment readily and freely available to smokers who request it. Trial registration ClinicalTrials.gov : NCT01429129 , Registered 2 September 2011; NCT03097445 , Registered 25 March 2017.